Identification Based Education Biblio Media Maladjustment Ego Counseling at SMP N 2 Silaut - Muqtazal, Barid (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the existence of students who do Maladjustments in their daily activities, namely students who have a perception that when they do not meet their needs, it is considered a negative thing. In addition, guidance and counseling (BK) teachers are also aware of the difficulties in uncovering adolescent problems. The purpose of this study is to identify adolescent Maladjustment based on ego counseling and develop a self-consulting-based Maladjustment tool. This research was conducted at SMPN 2 SILAUT, this type of research is research and development. The steps of this research researcherlimiting 5 development steps, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation (validated by 3 examiners), (5) design revision. Population of all students as many as 217 students. With sampling using purposive sampling technique with a total sample of 54 students. The instrument used in this research is a questionnaire, while for data analysis using descriptive statistics with percentage techniques. The results of the research on the development of Maladjustment tools based on ego counseling in SMPN 2 SILAUT seen from the results of the identification of adolescent Maladjustments based on ego counseling in general are on a few criteria. Based on this research, it is recommended for BK teachers to further minimize Maladjustment by testing the material designed through this research